Comparative study of the effect of TiO2 support composition and Pt loading on the performance of Pt/TiO2 photocatalysts for catalytic photoreforming of cellulose. (1st September 2021) - Lan, Lan; Daly, Helen; Jiao, Yilai; Yan, Yin; Hardacre, Christopher; Fan, Xiaolei
Abstract: Herein, catalytic aqueous phase photoreforming of cellulose was carried out over Pt/m-TiO2 ( i.e., mixed phase of anatase and rutile) and Pt/anatase catalysts to investigate the effect of the TiO2 support structure and Pt loading on the production of H2 . The effect of the TiO2 support on the properties of the resulting Pt/TiO2 catalysts (such as actual Pt loading and BET surface area) was not significant. At low Pt loading of 0.16 wt.%, the TiO2 supports affected the sub-nanometre Pt structures which was confirmed by the diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) characterisation (using CO as the probe). Conversely, the effect of TiO2 supports on larger Pt particles (on 1 wt.% catalysts) was insignificant possibly due to the reduced effect of restructuration of bigger Pt particles on the TiO2 supports. With an increase in Pt loading from 0.16 wt% to 1.00 wt.%, the normalised H2 production rate (with respect to the actual supported Pt amount and specific surface area of the catalysts) showed a decreasing trend over the two types of the catalysts, i.e., from 10.6 to 1.4 μmol h −1 m −2 mgPt −1 for Pt/m-TiO2, and from 8.5 to 1.2 μmol h −1 m −2 mgPt −1 for Pt/anatase. Specifically, large Pt particle sizes reduced the CO2 /H2 production from cellulose photoreforming over both Pt/m-TiO2 and Pt/anatase catalysts, indicting an important role played by Pt particle size in photoreforming. Interestingly, in this study, the m-TiO2 supported catalysts only showed the benefits of enhanced charge separation across the phase junction in producing H2 with small Pt particles (at sub-nanometre), whilst, when large Pt particles (at around 1–2 nm) were supported, such a benefit was not significant in cellulose photoreforming. The promoting effect of small, sub-nm particles is attributed to the better capture of photoelectrons from bulk TiO2 and better activity of H + coupling on small Pt particle. Further fundamental study on such guest-host interactions is devised to optimise Pt/TiO2 catalysts for improving H2 production from photoreforming reactions. Graphical abstract: Image 1 Highlights: Nature of TiO2 supports affect Pt structures at low Pt loading of 0.16 wt.%. CO-DRIFTS characterisation shows the Pt structures on different TiO2 supports. Normalised rate over surface area and Pt loading for comparing photoreforming activity.